Correlation Between Parenting Pattern of Working Moms and Children's Independence at Kindergarten Hang Tuah 1 Surabaya - Widianingtyas, Sisilia Indriasari; Widayati, Marcellina Rasemi; Wahyuni, Lucia Dwi Sri (STIKES Adi Husada, 2024)
Social and economic changes in modern society have increased the number of parents working outside the home. This phenomenon has a significant impact on family dynamics and parenting patterns. One important aspect that needs to be investigated is how working parents affect the development of children's independence. Independence is an important aspect of child development, including the ability to make decisions, solve problems, and take responsibility for their actions. This study aims to explore the correlation between the parenting pattern of working moms and children's independence aged 5-6 years. This research is an observational study (non-experimental) with a cross-sectional research design. This study aims to examine the correlation between parenting patterns of working mothers (independent variable) and the independence of children aged 5-6 years (dependent variable). The research was conducted at Hang Tuah 1 Surabaya Kindergarten. The instruments used in this study were a modified Parenting Styles and Dimensions Questionnaire-Short Version (PSDQ) and a questionnaire for children's independence. The statistical test used in this study is Spearman analysis. After processing the data using the spearman's rho test the results obtained p = 0.036 <0.05. These results, show that there is a correlation between parenting patterns of working mothers and the independence of children aged 5-6 years at Hang Tuah 1 Surabaya Kindergarten. Working mothers should provide attention, affection, and warmth so that children's independence both in the home and school environment will be higher.